The new media and heterotopic technologies in the Philippines - Pertierra, Raul (Human Technology, 2008)
Information overload is perhaps the most common frustration of our age. It strikes everyone: young and old, educated and uneducated, rich and poor, first world and third world. Human communication has taken on the qualities of the supernatural. Indeed it has surpassed it! Zeus could only rely on Mercury's speed to convey his commands; presently electronic messages zip around the globe and the universe at the speed of light. No wonder that new communication technologies often evoke notions of the supernatural. This paper deals with some of the unexpected effects of the new communication technologies, in particular for mobile phones. While the mobile has become the icon of connectedness, it also serves as the index of our disconnectedness with mundanity. This apparent contradiction generates inevitable anxieties often linked to the supernatural or the otherworldly.